Análisis de la fotografía difundida en los medios impresos y su sustento periodístico para informar a la ciudadanía lojana, período marzo-agosto de 2014. Propuesta alternativa - GUAMÁN CORREA, ÁNGEL RUPERTO (2015)
The photograph in the environment of the media is very important because it allows viewing, objectively and directly, the reality of the facts and events that are told in a news story. When a reporter writes a note and supports a picture, it must have the necessary elements of form and substance to be useful and clear to the audience. Undeniably, images and photographs are published in the print media are an important contribution to its content and aesthetics. Well it is said that "a picture is worth a thousand words." The problem is when the photographs published in the written media does not contain enough journalistic support, which hurts the understanding of readers and can distort the meaning of the article. With the results of the field work it was determined that the photographs were published in the local print media, in large part, do not link properly with the text, do not enhance the information note and provide meaningful data to the written text.